Pengaruh Pembiayaan Mudharabah, Musyarakah dan Murabahah Terhadap Profitabilitas Bank Umum Syariah - Dinar Mega Silvia Sari; Sri Suartini; Isro’iyatul Mubarokah; Nanu Hasanuh (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the effect of mudharabah, musyarakah, and murabahah financing on the level of profitability in banks using the Return on Assets (ROA) ratio simultaneously and partially. The sample used in this study was 42 data from the results of the outlier test which previously had 52 sample data into 42 sample data with the study population using 7 (seven) Islamic commercial banks until 2019. The data analysis method used in this study was multiple linear regression of panel data. The results of this study indicate that partially mudharabah financing has no significant negative effect on the level of profitability, while musharaka partially has a negative effect on the level of profitability. Murabahah financing has a significant positive effect on profitability.